2022
DOI: 10.1002/chem.202103897
|View full text |Cite
|
Sign up to set email alerts
|

Indeno[2,1‐a]fluorene‐11,12‐dione Radical Anions: Synthesis, Characterization, and Properties

Abstract: The one‐electron reduction of indeno[2,1‐a]fluorene‐11,12‐dione (IF) with various alkali metals prepare the radical anion salts. The data about different structures, properties, and characterization was obtained by single‐crystal X‐ray diffraction, electron paramagnetic resonance (EPR) spectroscopy, superconducting quantum interference device (SQUID) measurements, and physical property measurement system (PPMS). Compound IF.−K+(18‐c‐6) is regarded as a one‐dimensional magnetic chain through C−H⋅⋅⋅C interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…(ii) The bonds in the hmtt ligand also showed variations in length, which meant that they were also involved in the photochromism. (iii) While we cannot be certain which fraction of the ligands in these MOFs undergo a change, the bond length modifications in these MOFs are consistent with those reported for organic pyrene-fused azaacene and indeno­[2,1- a ]­fluorene-11,12-dione radical anions and N , N′ -diphenyldihydrophenazine radical cations. …”
Section: Resultsmentioning
confidence: 99%
“…(ii) The bonds in the hmtt ligand also showed variations in length, which meant that they were also involved in the photochromism. (iii) While we cannot be certain which fraction of the ligands in these MOFs undergo a change, the bond length modifications in these MOFs are consistent with those reported for organic pyrene-fused azaacene and indeno­[2,1- a ]­fluorene-11,12-dione radical anions and N , N′ -diphenyldihydrophenazine radical cations. …”
Section: Resultsmentioning
confidence: 99%
“…23 Previous reports have shown that introducing nitrogen atoms or electron-withdrawing groups into the polycyclic aromatic hydrocarbon (PAH) aids in the formation of stable radical anions. [24][25][26][27][28][29][30][31][32] It is well known that spin delocalization can improve the stability of radical anions, particularly for large planar structures, such as PAHs, due to the conjugation effects. In addition, the dimerization reaction of two bowlshaped PAH monoanion radicals was first reported in 2018 by the Petrukhina and Rogachev groups.…”
Section: Introductionmentioning
confidence: 99%